2014
DOI: 10.1051/epjconf/20147200018
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Tau Lepton Physics

Abstract: Abstract. The τ lepton is the heaviest of the charged leptons and the only one to decay into hadrons. This provides a unique opportunity to probe low energy QCD and the charged weak interaction of both the relative coupling strength to the first and second generation of quarks and to the lepton. Moreover, many new physics scenarios couple primarily to the third generation, making it a promising prospect for new physics searches. In this paper, an overview of recent measurements of the τ lepton from BABAR, BELL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 63 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The review of the different aspects of τ physics can be found in Refs. [1,2] . In the last years, the interest to different τ decays is stimulated by the plans to construct and run Super KEKB (Japan), Super c − τ (Russia) and Super c − τ (HIEPA, China) facilities [3][4][5][6] , where it will be accumulated more than 10 10 events with polarized τ, and the modern status of these facilities is discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of the different aspects of τ physics can be found in Refs. [1,2] . In the last years, the interest to different τ decays is stimulated by the plans to construct and run Super KEKB (Japan), Super c − τ (Russia) and Super c − τ (HIEPA, China) facilities [3][4][5][6] , where it will be accumulated more than 10 10 events with polarized τ, and the modern status of these facilities is discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The left (middle) panel corresponds to description of the vector and axial-vector form factors chosen in Ref [17]. which labeled as set 1(2). The form factors used in the right panel differ by accounting ρ ′ in the vector form factor and a 1 propagator in the axial-vector form factor as explained in text, and we label them as the set 3.…”
mentioning
confidence: 99%